2016
DOI: 10.1597/12-290
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recombinant Human Bone Morphogenetic Protein-2 and Adipose Tissue-Derived Stem Cell on New Bone Formation in High-Speed Distraction Osteogenesis

Abstract: This study suggests that the use of rhBMP-2 in combination with or without ADSC is helpful to promote bone regeneration in high-speed distraction osteogenesi s of adult rabbit cranium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“… 15 , 49 The number of transplanted cells ranged from 1 to 30×10 6 . The cell injection timing included three different time points: in three studies, MSCs were injected during the distraction phase 15 , 37 , 49 or during the consolidation phase; 30 , 38 , 43 , 44 , 45 , 47 , 48 , 51 in three studies, the MSCs were injected on the day of the operation; 16 , 20 , 50 and in one study the time of injection was not stated 52 . The majority of the studies reported that MSC transplantation at the end of the lengthening phase with MSCs over 1 x 10 6 enhanced bone consolidation or formation in DO in animal models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 , 49 The number of transplanted cells ranged from 1 to 30×10 6 . The cell injection timing included three different time points: in three studies, MSCs were injected during the distraction phase 15 , 37 , 49 or during the consolidation phase; 30 , 38 , 43 , 44 , 45 , 47 , 48 , 51 in three studies, the MSCs were injected on the day of the operation; 16 , 20 , 50 and in one study the time of injection was not stated 52 . The majority of the studies reported that MSC transplantation at the end of the lengthening phase with MSCs over 1 x 10 6 enhanced bone consolidation or formation in DO in animal models.…”
Section: Resultsmentioning
confidence: 99%
“…Dehghan et al, 36 Lee et al, 51 and Kinoshita et al 37 used the higher rate of lengthening, and the MSC therapy significantly promoted new bone formation and shortened the consolidation period in their DO models.…”
Section: Discussionmentioning
confidence: 99%
“…First, only one injection time point was evaluated. Most previous studies have implanted cells into the distraction gap during either the distraction [11,14,20] or consolidation [12,13,15,16,19,23] phases. It is possible that exogenous MSCs do not play a significant role so early in latency, and systemic administration would be effective during later phases.…”
Section: Discussionmentioning
confidence: 99%
“…A body of pre-clinical research over the past 20 years indicates that addition of cells enhances the amount and quality of new bone generated by DO. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] These studies have used stem cells or osteogenically differentiated cells with success. This has been shown in both mandibular [12,13,[16][17][18][19]25,26] and long bone distraction [11,14,15,[20][21][22][23][24] and could theoretically decrease the consolidation time.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce complication and improve the bone healing, several regenerative techniques have been associated with DO protocols. Low level laser therapy has been showed to reduce the time for bone regeneration of the DO in rabbits, gene therapy like addition of BMPs on the lengthened callus are reported to be able to accelerate bone maturation with different levels of success and cost [13,28] .…”
Section: Discussionmentioning
confidence: 99%